Century of the Communist Party of China and the perspective of socialism with a Chinese specificity - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2021)
The article analyses the main directions and paths of Chinese modernisation, the features of the US’ opposition to it, it is concluded that the success of socialism with Chinese characteristics creates a new world situation in which new socio-economic civilisational foundations can create a society of socialist orientation. It is noted that Deng Xiaoping, without holding any government posts, being only the chairman of the CPC Central Committee’s Defense Committee, led the process of Chinese modernisation, which brought China to the forefront of scientific, technological and social progress in the world. The author argues that the basis of Chinese success is the Leninist formula of the NEP – the use of private entrepreneurship under the control of a socialist state in order to develop at an accelerated rate of social wealth in the amount necessary to meet the basic life needs of its citizens. The path of China was fraught with many unsuccessful and tragic experiments, therefore the current socio-economic leap forward in civilisation is an unprecedented event in world history. The implementation of goals and objectives of such a global scale will make serious changes in the world order, and require a new political philosophy. The success of socialism with Chinese characteristics within the country, as well as in programs to support the progressive development of countries and peoples of the world ready for cooperation, allows us to give a cautious optimistic assessment of the future Chinese perspective. And this, according to the author, is today a clear threat to the tasks and goals of American domination in the world.